The Effects of Whole Body Vibration Training and Creatine Supplementation on Lower Extremity Performance and Balance in Elderly Males - Mostafa Rahimi; Mohammadreza Kordi; Noraldin Karimi; Abbasali Gaeini; Ali Samadi; Nasim Ali moradi (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The purpose of this study was to investigate the effects of whole body vibration training (WBVT) and creatine (Cr) supplementation on lower extremity performance and balance in elderly males. Methods & Materials: In this semi-experimental study, twenty two eligible males from the members of an elderly daycare center with more than 60 years of age were enrolled and were divided into three groups randomly, WBVT+Cr(n=7), WBVT+Pgroup (n=7), and control group (n=8). In WBVT+Cr and WBVT+P groups exercises were performed on the whole body vibration device for 10 days with 30-35 Hz intensity and 5 mm amplitude. The WBVT+Cr group consumed 20g/day Crsupplement for the first 5 days followed by 5g/days for the next 5 days of protocol. The WBVT+P group consumed dexterous. The control group neither did any exercise nor consumed any supplement during the protocol. Static balance by standing time on one leg, dynamic balance by TUG test and lower extremity performance by 30-meter walking test, sit and stand test and tandem gait test weremeasured. Paired sample t-test and one way ANOVAwere used for data analysis (α=0.05). Results: Our results showed that dynamic balance, lower body performance in 30- meter walking and tandem gait improved in experimental groups. However, ANOVA did not show any significant increase in static balance (P=0.514), dynamic balance (P=0.153), lower body performance in 30-meter walking test (P=0.339), sit and stand test (P=0.578) and tandem gait (P=0.151). Conclusion: In conclusion, it seems that WBVT plus Cr supplementation improves some of the motor fitness factors in elderly males during a short time.